O’TKIR HASHIMOV’S MASTERPIECE "LIVES PASSED IN A DREAM" IS A DEEP LOOK AT THE FATE OF THE ERA - Azamatova Muxlisa Ilyos qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: O'tkir Hashimov, one of the sharpest writers of the 20th century, wrote in first years of independence, the work " Lives passed in a Dream" exposes some superstitions hidden in the depths of the past and the fate of people living in the 20th century aimed at reflecting the complexities. The work begins with a unique image. "Autumn is like a patient on his deathbed. Sick tinders groan under its feet... Realizing that all its efforts have been wasted, it looks at the world sadly. A white mist like a shroud covers the earth. From among the white darkness, the uncharacteristic crowing of crows is heard.'' This beginning seems to decide the fate of the whole work... The lines drawn like the preparation of nature for a deep sleep after the autumn has finished its work, represent the fundamental turns of the heroes' lives. The likeness of autumn to a patient lying on the death bed, the moaning of old leaves of trees, the white fog covering the earth and the sky like a shroud, the careless crowing of crows indicate that there are some unconscious situations in the play.